Producer Breeding Objectives and Optimal Sire Selection - Tozer, P.R.; Stokes, J.R. (Journal of dairy science, 2002)
Information from an online survey of dairy producers was used to determine how important producers perceived three different objectives in the breeding problem. The objectives were: maximizing expected net merit of the progeny, minimizing the expected progeny inbreeding coefficient, and minimizing semen expenditure. Producers were asked to rank the three objectives and then to weight the importance of each objective relative to the others. This information was then used to determine weights to be used in a multiple-objective integer program designed to select individual mates for a herd of 76 Jersey cows with known genetic background and cow net merit. The results of the multiple-objective models show that rank and relative importance of producer objectives can affect the portfolio of sires selected. Producers whose primary objective was to maximize expected net merit had a range of average expected progeny net merit of $306 to $310, but the level of expected progeny inbreeding was from 6.99 to 10.45%, with a semen cost per conception of $35 to $41. For producers who selected minimizing progeny inbreeding as the primary goal in their breeding programs, the range of inbreeding was from 6.11 to 6.60%, with lower net merit range of $274 to $301 and semen expenditure of $30 to $37 per conception. One producer selected minimizing semen cost as the primary objective. For that producer's portfolio, the semen cost was $27 per conception and net merit was $288, with a progeny inbreeding coefficient of 10.68%. The results of this research suggest that producer information and goals have a substantial impact on the portfolio of sires selected by that producer to attain these goals.